OSL, TL and IRSL emission spectra of sedimentary quartz and feldspar samples - Lomax, Johanna; Mittelstraß, Dirk; Kreutzer, Sebastian; Fuchs, Markus (Radiation measurements, 2015)
This contribution presents a variety of different luminescence emission spectra from sedimentary feldspar and quartz samples under various stimulation modes. These are green stimulated quartz (OSL-) spectra, quartz TL spectra, feldspar IRSL and post-IR IRSL spectra. A focus was set at recording OSL and IRSL spectra at elevated stimulation temperatures such as routinely applied in luminescence dating. This was to test whether optical stimulation at elevated temperatures results in a shift of emission peaks. For OSL emissions of quartz, this has so far not been tested. In case of feldspar emissions, post-IR IRSL conditions, hence IRSL emissions at a low temperature, directly followed by high temperature post-IRSL emissions, are explicitly investigated. All spectra were recorded using a new system incorporated into a Lexsyg luminescence reader. Thus, this study, besides presenting new spectral data, also serves as a feasibility study for this new device. It is shown that (a) the new device is capable of automatically measuring different sorts of spectra, also at elevated temperatures, (b) known thermally and optically stimulated peak emissions of quartz and feldspar are confirmed, (c) obtained IRSL and OSL spectra indicate that there is no significant relation between peak emission and stimulation temperature.
Online verfügbar: 25. Februar 2015, Artikelversion: 21. Oktober 2015
Gesehen am 31.03.2025